ANALYSIS OF FARMERS' HEMP GROWING TENDENCIES AND EXPECTATIONS: THE CASE OF TÜRKİYE - Esra YAZICI; Sait ENGINDENIZ; Duran GÜLER (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The purpose of this study is to analyze the factors affecting the tendency of farmers to grow hemp in Rize province of Türkiye. The data was collected by face-to-face survey method from 90 farmers with proportional sampling. A five-point Likert scale was used to evaluate farmers' knowledge levels, opinions and attitudes regarding hemp growing, and their tendencies and expectations towards hemp growing. Best-Worst analysis was performed to determine the most important support practices that farmers expect from the government to grow hemp. The Fuzzy Paired Comparison method was used to determine which criteria farmers will attach importance to when growing hemp. According to the study results, 46.7% of the farmers have grown hemp before. However, it has been determined that farmers need more information about hemp growing. 48.9% of farmers are willing to grow hemp individually and 35.6% under contract. Farmers do not find the current supports sufficient and think that they should be diversified. For example, land use, seed supply and grant support are among their expectations. 36.6% of farmers think that hemp growing is profitable. 56.6% of farmers argue that hemp growing will not be more profitable than other products such as tea and hazelnuts. 56.7% of farmers stated that they would turn to hemp growing if government support was increased. The most important criteria that farmers will consider for growing hemp are climate conditions, soil structure and yield, respectively. For hemp growing to develop in this region, farmers' expectations regarding supports and market alternatives must be met.